Climate change awareness and adaptation strategies of banana, pineapple and mango farmers in northern and southern Mindanao - Wahing, Geraliza D.; Digal, Larry N. (2018)
Climate change is a widely-researched phenomenon and a prominent issue that the world has been facing. It brought changes in climate patterns such as increasing temperature, rainfall, and humidity, and brought negative effects to the environmental, social, and agricultural sectors. The Philippines is a top producer and exporter of high-valued agricultural commodities such as banana, pineapple, and mango. However, the ranked 3rd in the most climate change vulnerable countries in the world. In order to lessen climate change negative effects, farmers engaged in different adaptive measures such as enhancing farm management and increasing farm inputs. The purpose of the study was to assess the climate change awareness and adaptation strategies of farmers in Northern and Southern Mindanao regions that are top producers of tropical exports commodities such as banana, pineapple and mango. The Multivariate Linear regression was used in order to extract the significant factors that affect adaptation strategies. Moreover, Stata 12, FsQCA, and NVIVO software were used for further analysis. The collection of data was done through a focused group discussion and personal interviews using a survey questionnaire. A total of 80 respondents were interviewed. The result shows that 48.75% of the respondents have low awareness of the climate change. Whereas, 51.25% of the respondents have an average awareness of the climate change. Furthermore, farmers perceived that climate change increases pest and diseases outbreaks, decrease in income, and increase the cost of farm inputs. Study suggests that government should focus on providing crop insurance. The identified stakeholders should provide farmers? access to finance and marketing. Further, increasing the farmers? level of awareness through service extensions is one of the highly-recommended interventions.
Thesis (BS Agribusiness Economics) -- University of the Philippines Mindanao, May 2018